A Theoretical and Structural Investigation of Thiocarbon Anions - Chen, Zhongfang; Sutton, Liam; Moran, Damian M.; Hirsch, Andreas; Thiel, Walter; Schleyer, Paul (Journal of Organic Chemistry, 2003)
Density functional theory energies, geometries, and population analyses as well as nucleus-independent chemical shifts (NICS) have been used to investigate the structural and magnetic evidence for cyclic CS - and CS (n = 3-6) electron delocalization. Localized molecular orbital contributions to NICS, computed by the individual gauge for localized orbitals method, dissect π effects from the σ single bonds and lone pair influences. CS (n = 3-5) structures in D symmetry are minima. Their aromaticity decreases with increasing ring size. C S is both σ and π aromatic, while CS and CS are much less aromatic. NICS(0)π, the C-C(π) contribution to NICS(0) (i.e., at the ring center), decreases gradually with ring size. In contrast, cyclic CS prefers D symmetry due to the balance between aromaticity, strain energy, and the S-S bond energies and is as aromatic as benzene. The theoretical prediction that CS has D minima was confirmed by X-ray structure analysis. Comparisons between thiocarbons and oxocarbons based on dissected NICS analysis show that CS (n = 3-5) and CS are less aromatic in D symmetry than their oxocarbon analogues.